1991
DOI: 10.1079/bjn19910098
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a nutritionally-balanced cassava (Manihot esculenta Crantz) diet on endocrine function using the dog as a model 2. Thyroid

Abstract: _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _Growing dogs were divided into three groups and were fed on nutritionally-balanced diets. Control dogs were fed on a rice diet, the cassava (gari) group ate a diet in which gari provided the carbohydrate source, while the rice +cyanide group consumed the rice diet to which hydrocyanic acid (equivalent to that present in gari) was added. Each group consumed its diet for 14 weeks, during which plasma thiocyanate concentration and total serum triiodothyronine (T3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…Gluconeogenesis from protein was five and two times greater in the gari-fed and rice plus cyanide-fed dogs respectively, relative to the rice-fed control dogs (Kamalu, 1991). Although the reasons for the differences observed in the responses of the different muscles to either the gari or rice plus cyanide diets are not known for sure, the present findings, as well as the biochemical and histopathological differences previously reported in the gari-and rice plus cyanide-fed dogs (Kamalu, 1991;Kamalu & Agharanya, 1991), suggest that the metabolic fate and effects on muscle development of organic and inorganic dietary cyanide in the dog may differ. This agrees with the observations of Tewe & Maner (1981) on the effects of organic and inorganic cyanide on muscle development, but is contrary to the observations of Ermans et al (1973) who reported that the metabolic fate of hydrocyanic acid closely resembles that of inorganic cyanide in single-stomached animals.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Gluconeogenesis from protein was five and two times greater in the gari-fed and rice plus cyanide-fed dogs respectively, relative to the rice-fed control dogs (Kamalu, 1991). Although the reasons for the differences observed in the responses of the different muscles to either the gari or rice plus cyanide diets are not known for sure, the present findings, as well as the biochemical and histopathological differences previously reported in the gari-and rice plus cyanide-fed dogs (Kamalu, 1991;Kamalu & Agharanya, 1991), suggest that the metabolic fate and effects on muscle development of organic and inorganic dietary cyanide in the dog may differ. This agrees with the observations of Tewe & Maner (1981) on the effects of organic and inorganic cyanide on muscle development, but is contrary to the observations of Ermans et al (1973) who reported that the metabolic fate of hydrocyanic acid closely resembles that of inorganic cyanide in single-stomached animals.…”
Section: Discussionsupporting
confidence: 55%
“…A decrease in thyroid hormone level is also associated with a decrease in the levels of various lysosomal proteases like cathepsin B ( E C 3.4.22.1) and D ( E C 3.4.23.5) in the liver and muscles (DeMartino & Goldberg, 1978). However, the hypothyroidism observed in the rice plus cyanide-fed dogs was not associated with reduction in muscle mass suggesting that the rice plus cyanide diet probably contained enough dietary protein for both cyanide detoxification and other body needs as indicated by findings of the highest level of free plasma amino acids (phenylalanine and tyrosine) in this group (Kamalu & Agharanya, 1991). In addition, Goldberg et al (1980) reported that an alteration of thyroid hormone level is usually associated with synchronous 2-3-fold alteration in the levels of a variety of lysosomal enzymes, and suggested that this may be responsible for the various unexplained effects of the thyroid hormone in disease conditions.…”
Section: Discussionmentioning
confidence: 71%
“…Another possibility is a neuronal accumulation of cyanide, which was observed earlier in in vitro studies (Borowitz et al, 1994). Long-term cyanogenic plant consumption by both men (Adewusi and Akindahunsi, 1994) and animals (Bahri, 1987;Kamalu and Agharanya, 1991) has been associated with the development of hypothyroidism. Thiocyanate, the main cyanide metabolite, is thought to be responsible because it competes with iodide in the thyroid gland (Delange and Ermans, 1996).…”
Section: Discussionmentioning
confidence: 92%
“…Long-term cyanogenic plant consumption by both humans (Adewusi and Akindahunsi, 1994) and animals (Bahri, 1987;Kamalu and Agharanya, 1991) has been linked to the development of hypothyroidism and goiter. In the present work, goats treated with chokecherry and thiocyanate had an increased number of vacuoles in the colloid of thyroid glands, which was similar to earlier studies (Soto-Blanco et al, 2001a; Means for each day in the same column preceded by different superscript letters are significantly different (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%